2021
DOI: 10.3389/fimmu.2021.662901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peptide-Induced Immune Tolerance on Murine Lupus

Abstract: The regulation of autoimmunity and the molecular mechanisms by which different immune cells, including T cells, polymorphonuclear leukocytes (PMN-granulocytes), and B cells suppress autoimmune diseases is complex. We have shown previously that BWF1 lupus mice are protected from autoimmunity after i.v. injection or oral administration of tolerogenic doses of pCons, an artificial synthetic peptide based on sequences containing MHC class I and MHC class II determinants in the VH region of a J558-encoded BWF1 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 89 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…T regs secrete inhibitory cytokines such as IL-10, TGF-β, and IL-35 that can suppress target cells including APCs and CD4 + CD25 − T effector cells. [ 68 , 69 , 125 , 126 ] For example, pCons-induced T regs secreted TGF-β and IL-10, [ 6 , 8 , 18 , 21 , 76 ] is also observed in other studies. [ 70 , 71 , 72 ]…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…T regs secrete inhibitory cytokines such as IL-10, TGF-β, and IL-35 that can suppress target cells including APCs and CD4 + CD25 − T effector cells. [ 68 , 69 , 125 , 126 ] For example, pCons-induced T regs secreted TGF-β and IL-10, [ 6 , 8 , 18 , 21 , 76 ] is also observed in other studies. [ 70 , 71 , 72 ]…”
Section: Introductionmentioning
confidence: 63%
“…We reported that both CD4 + and CD8 + T regs are functionally deficient in both BWF1 mice and patients with SLE (they are as well reduced in other autoimmune conditions). [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 76 , 77 , 78 ] While CD4 + T regs have been intensively studied, [ 63 , 64 , 65 , 66 , 67 ] less is known about the CD8 + T regs in the suppression of autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the direction of mitogen-induced change in expression was reversed for a proportion (<2%) of differentially expressed genes irrespective of the test oil supplement. Two of the most down-regulated transcripts were considered anomalies, namely CD163, which is a macrophage-specific scavenger receptor [ 48 ], and CD1d, a marker expressed by antigen-presenting cells including CD19 + CD1d + regulatory B lymphocytes [ 49 ] that is also a target for invariant natural killer T cells [ 50 ]. One possible explanation is that there was low-level contamination of the T cell preparations with macrophages or CD1d + B cells that was not detected by routine assessment of the purity of the T cell preparation by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…A safe alternative to the use of drugs carrying important side effects has been the use of peptide-based tolerogenic therapeutics for the induction of immune tolerance to self-antigens though the inhibition of autoreactive T, B, and dendritic cells together with the promotion of the activity of immunoregulatory cell populations. [ 9 , 10 , 11 ] We discuss below the promise of peptide-based immunotherapies and related clinical trials.…”
Section: Introductionmentioning
confidence: 99%